(untitled) (Research, Society and Development, 2020)
The present work points to the scientific production (theses and dissertations) on the Teaching of Chemistry, emphasizing the categories in the direction of the use of media resources, cataloged on the Capes Portal from 2012 to 2016. We opted for a qualitative bibliographic analysis, considering how the target audience, students with disabilities and students without disabilities, supported by a categorization of five topics, relating the teaching of chemistry according to the teaching-learning process described in academic production. The results indicate a greater need for investigation and research in the area of concentration related to students with disabilities, as only 14% of the studies analyzed have this theme. According to the representation of a methodological approach, interwoven according to the following categories: (32%) (Information and Communication Technologies (ICTs) (21%); Concept Maps (17%); Videos (21%); Software (21%) and (7%) Blogs, showing a qualitative (67%) or mixed (32%) approach, specified in the research productions, cataloged in the production of this article. We conclude that, as Chemistry teachers, we have the opportunity to use media tools, teach classes in the context of inclusion.